Review of Treasures from the Sea: Sea Silk and Shellfish Purple Dye in Antiquity, ed. H. L. Enegren and F. Meo - Kate Fulcher (Papers from the Institute of Archaeology, 2017)
Treasures from the Sea: Sea silk and shellfish purple dye in antiquity, ed. H. L. Enegren and F. Meo, Oxford; Havertown: Oxbow Books, 224 pages (Hardbound), £38, US55, 2017, ISBN: 978-1785704352. This volume presents the proceedings of a conference in Lecce in 2013, which brought together several different approaches including archaeology, experimentation, scientific analysis, and terminology. This interdisciplinary approach is reflected in the publication, which both maintains the reader’s interest and works well for ancient materials.